MIDGLEY AT THE INTERSECTION OF ANIMAL AND ENVIRONMENTAL ETHICS - McELWAIN, GREGORY (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2018)
This paper explores the intersection of animal and environmental ethics through the thought of Mary Midgley. Midgley’s work offers a shift away from liberal individualist animal ethics toward a relational value system involving interdependence, care, sympathy, and other components of morality that were often overlooked or marginalized in hyperrationalist ethics, though which are now more widely recognized. This is most exemplified in her concept of “the mixed community,” which gained special attention in J. Baird Callicott’s effort to create a “unified environmental ethics.” In this, Callicott saw the potential in Midgley’s thought for bringing animal and environmental ethics “back together again.” However, this paper argues that he oversimplified and misapplied her complex concept. This is primarily due to his attempt to harmonize her approach with a rigid dichotomy between domestic and wild animals—as well as one between individuals and collectives—in his conception of the land ethic in the tradition of Aldo Leopold. Throughout, this paper also highlights Midgley’s value as an early contributor to the convergence of animal and environmental ethics.